Mathématiques
jonami
18

Développement avec un peu d'étapes : A (x) = (x -4) (3x +1) - (4 - 5x) (2x +3) B (x) = (2x -3) au carré - (x +4) au carré C (x) = 3 (2x -1) au carré - 2 (1+x) au carré

+1
(1) Réponses
Mzllealycia

Salut, A (x) = (x -4) (3x +1) - (4 - 5x) (2x +3) A(x) = 3x² + x - 12x - 4 - (8x + 12 -10x² -15x) A(x) = 3x² - 11x - 4 - ( -7x + 12 -10x²) A(x) = 3x² - 11x - 4 + 7x - 12 + 10x² A(x) = 13x² - 4x - 16 B (x) = (2x -3)² - (x +4)² B(x) = 4x² - 12x + 9 - (x² + 8x + 16) B(x) = 4x² - 12x + 9 - x² - 8x - 16 B(x) = 3x² - 20x - 7 C (x) = 3 (2x -1)² - 2 (1+x)² C(x) = 3(4x² - 4x + 1) - 2(1 + 2x + x²) C(x) = 12x² - 12x + 3 - (2 + 4x + 2x²) C(x) = 12x² - 12x + 3 - 2 - 4x - 2x² C(x) = 10x² - 16x + 1 Bonne journée !

Ajouter une réponse